MIKRODERMABRASI - Pandaleke, Thigita A.; Kapantow, Grace M. (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: Microdermabrasion is a skin rejuvenation procedure with a superficial abrasion mechanism to remove the outermost skin layer of the epidermis, exfoliation. The principle of skin rejuvenation with microdermabrasion is based on the principle of wound healing. Wounding and removing the outermost layer of the skin can stimulate the regeneration of new healthy cells from the epidermis and dermis. Microdermabrasion is usually used for a variety skin problems inter alia acne scars, hyperpigmentation, stretch marcks, and photodamaged skin. Microdermabrasion can be used on several areas of the skin, including the face, neck, chest, and hands.Keywords: microdermabrasion, rejuvenation, exfoliativeAbstrak: Mikrodermabrasi adalah prosedur peremajaan kulit superfisial dengan mekanisme abrasi yaitu membuang lapisan paling luar dari epidermis, dikenal sebagai eksfoliasi. Prinsip peremajaan kulit dengan mikrodermabrasi didasarkan pada prinsip penyembuhan luka. Melukai dan menghilangkan lapisan kulit paling luar dapat menstimulasi regenerasi pembentukan sel-sel baru yang sehat dari epidermis dan dermis. Mikrodermabrasi biasanya digunakan untuk berbagai permasalahan kulit seperti skar akne, hiperpigmentasi, stretch marck, serta photodamaged. Mikrodermabrasi dapat digunakan pada area kulit termasuk wajah, leher, dada, maupun tangan.Kata kunci: mikrodermabrasi, peremajaan kulit, pengelupasan